50.3k views
2 votes
Can someone help me with question2

Can someone help me with question2-example-1
User SahalMoidu
by
6.3k points

1 Answer

4 votes
We can manipulate both equations in order to make them in terms of y, and then substitute it in.

y+3x=-5 \\4x+2y=-8 \\Manipulate \ the \ first \ one \\ 3x = -y-5 \\ x = (-y)/(3)-(5)/(3) \\ Substitute \\ 4((-y)/(3)-(5)/(3)) + 2y = -8 \\ Manipulate \ the \ second \ equation \\ 4x = -2y-8 \\ x = (-2y)/(4)-2 \\ x = (-y)/(2)-2 \\ Substitute \\ y+2((-y)/(2)-2)=-5
The answers are answer choice A and D
User Dmitry Shopin
by
7.0k points